Preservação arqueológica e ação educativa nas Missões - Moraes, Tobias Vilhena de (2014)
This research aims to mainly analyze for the real first time the trajectory of ideas and concepts for the Archaeological Preservation of the material culture remainings in the Jesuit-Guarani Missions located in the Brazilian territory. From the results obtained through several excavations, noting the historical construction of legal and technical regulations, it will be analyzed how continuous management programs of the archaeological heritage over the years contributed to consolidate a new approach of the national archaeological heritage. Finally, we look at how the management of archaeological heritage has built a growing interface with another important area of the field of cultural heritage preservation: education. This is a broad perspective, but recognizes the complexity of human beings in their different ways of knowing and acting and which considers Archaeological Science and Education active interlocutors in the development of a critical reflection of the past